Weight Loss and Gastrointestinal Hormone Variation Caused by Gastric Artery Embolization: An Updated Analysis Study - Tang, Yi; Pan, Xiaohui; Peng, Ge; Tong, Nanwei (Frontiers in Endocrinology, 2022)
Objective: Many gastric artery embolization (GAE) surgeries have been performed in recent years. We try to determine whether GAE leads to weight loss by decreasing gastrointestinal hormones through the analysis of weight loss and gastrointestinal hormone changes. Methods: The PubMed and Medline databases, and the Cochrane Library, were searched using the following keywords. A total of 10 animal trials (n=144), 15 human trials (n=270) were included for analysis. After GAE, we mainly evaluated the changes in body weight loss (BWL) and body mass index (BMI), as well as metabolic indexes, such as blood glucose, lipids, and gastrointestinal hormones levels. Results: Animal subjects received either chemical or particle embolization, while human subjects only received particle embolization. In animal trials (growing period), the GAE group gained weight significantly slower than the sham-operated group，ghrelin levels decreased. In human trials, GAE brought more weight loss in the early stages, with a trend towards weight recovery after several months that was still lower than baseline levels. Besides weight loss, abnormal metabolic indicators, such as blood glucose and lipids were modified, and the quality of life (QOL) scores of obese patients improved. In addition, weight loss positively correlates with ghrelin. Conclusion: GAE may help people lose weight and become a new minimally invasive and effective surgery for the treatment of obesity, but may be less effective for severe obesity. Gastrointestinal hormones level such as ghrelin change may be a mechanism for weight loss in GAE.